ON SOCIO-ECONOMIC ASPECTS OF THE INDUSTRIAL REVOLUTION IN SCOTLAND IN THE XIX CENTURY - Marina Maximenko (Гуманитарные и юридические исследования)
The article studies certain socio-economic aspects of industrial revolution in Scotland in the 19th century. The topicality of industrial revolution in Scotland is explained not only by weak degree of study, but also various rates of its development as compared to the one in England. Industrialization problems in Scotland in the context of the British industrial revolution are partially highlighted in national scientific domain. It is remarkable that the industrial revolution in general differed in extreme unevenness and nonsynchronous speed of certain regions in Great Britain, but, undoubtedly, the achievement of progress and improvement of living conditions were the main outcomes. The article analyzes the influence of international relations on forming the local Scottish market, natural-geographic factor and also the growth of scientific knowledge and discoveries. The main objectives of the study are the identification of development features of industrial revolution in Scotland and peculiarities of development of such key industries as cotton production, metallurgy and railway construction. Moreover, an important task is to specify the influence of economic development on the Scottish society.